An evaluation of the efficacy of topical application of salicylic acid for the treatment of familial cylindromatosis. - Oosterkamp, H; Neering, H; Nijman, S; Dirac, A; Mooi, W; Bernards, R; Brummelkamp, T (2006)
BACKGROUND: Familial cylindromatosis is a rare genetic disorder, giving rise to neoplasms of the skin appendages. We have recently shown that loss of the cylindromatosis tumour suppressor gene leads to activation of NF-kappaB, a transcription factor having antiapoptotic activity. This provides a possible explanation for the deregulated growth of cylindromas. In cell-based assays, salicylate can prevent NF-kappaB activation caused by loss of the cylindromatosis gene, suggesting that salicylic acid application might be a potential treatment for cylindromatosis. OBJECTIVES: To assess the effectiveness of topical application of salicylic acid on familial cylindromas. METHODS: Cylindromas in five patients from four different cylindromatosis families were treated with twice daily and then once daily topical salicylic acid. Clinical response was determined by serial tumour measurements. RESULTS: In total 17 cylindromas in five patients were studied: 12 target lesions and five control lesions. The median size of the cylindromas was 1.0 cm (range, 0.6-2.8 cm). Two of the 12 cylindromas showed a complete remission. Another eight lesions showed some response, but not sufficient to qualify as partial remission. The control lesions remained stable or increased in size. CONCLUSIONS: Salicylic acid is a well-tolerated and potential new treatment for cylindromatosis.